2015
DOI: 10.1186/s12887-015-0362-3
|View full text |Cite
|
Sign up to set email alerts
|

Still births, neonatal deaths and neonatal near miss cases attributable to severe obstetric complications: a prospective cohort study in two referral hospitals in Uganda

Abstract: BackgroundNeonatal near miss cases occur more often than neonatal deaths and could enable a more comprehensive analysis of risk factors, short-term outcomes and prognostic factors in neonates born to mothers with severe obstetric complications. The objective was to assess the incidence, presentation and perinatal outcomes of severe obstetric morbidity in two referral hospitals in Central Uganda.MethodsA prospective cohort study was conducted between March 1, 2013 and February 28, 2014, in which all newborns fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
63
7
14

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(110 citation statements)
references
References 25 publications
26
63
7
14
Order By: Relevance
“…One The present high stillbirth rates are consistent with those of a previous Ugandan study, reporting 120 stillbirths per 1000 deliveries with severe complications in a referral hospital, but lower than those of a Nigerian study, which documented 211 stillbirths per 1000 deliveries with severe maternal morbidity in a tertiary hospital. 12,21 Furthermore, the present study supports earlier findings that preterm delivery is a risk factor for stillbirth. 22 Considering the high prevalence of preterm deliveries among women with complications, the number of stillbirths associated with preterm delivery may be greater than suggested previously.…”
Section: Discussionsupporting
confidence: 92%
“…One The present high stillbirth rates are consistent with those of a previous Ugandan study, reporting 120 stillbirths per 1000 deliveries with severe complications in a referral hospital, but lower than those of a Nigerian study, which documented 211 stillbirths per 1000 deliveries with severe maternal morbidity in a tertiary hospital. 12,21 Furthermore, the present study supports earlier findings that preterm delivery is a risk factor for stillbirth. 22 Considering the high prevalence of preterm deliveries among women with complications, the number of stillbirths associated with preterm delivery may be greater than suggested previously.…”
Section: Discussionsupporting
confidence: 92%
“…Stillbirth is a devastating pregnancy outcome that is estimated to occur in 2.65 million cases globally each year (17)(18)(19). In a recent Uganda research, it was reported that antepartum hemorrhage, ruptured uterus, severe preeclampsia, eclampsia, and the syndrome of hemolysis, elevated liver enzymes, low platelets (HELLP syndrome) had increased the risk of still birth or neonatal deaths (20). In the current study, the increase in stillbirth rate may be explained by better medical data records.…”
Section: The Main Risk Factors Related To Infant and Neonatal Mortalitymentioning
confidence: 48%
“…Pre‐eclampsia is characterized by an increase in blood pressure after the 20th week of pregnancy together with proteinuria, maternal organ dysfunction, and/or uteroplacental insufficiency . It is associated with high maternal morbidity and mortality and increases the risk of adverse perinatal outcomes …”
Section: Introductionmentioning
confidence: 99%
“…4 It is associated with high maternal morbidity and mortality and increases the risk of adverse perinatal outcomes. [5][6][7][8][9][10][11] Definitive treatment for pre-eclampsia is the delivery of the fetus.…”
Section: Introductionmentioning
confidence: 99%